COLLUSION DETECTION SOFTWARE IN ONLINE MULTIPLE CHOICE EXAMINATIONS – A REVIEW - Srinivasa Jayachandra (Медицина в Кузбассе, 2022)
Computers have been used in higher education to assess students for decades. Software to allow assessments to be delivered to students (often referred to as computer-assisted assessment, or CAA), became widely commercially available in the 1990s, and many institutions began to experiment with these packages. The increasing availability of networked computers by the mid-1990s allowed assessments and other educational services to be delivered online with web browsers but the problem of this online test is collusion and cheating. As on-line examinations become more popular, perhaps with the possibility of students being allowed to sit them remotely, the opportunity for cheating could be much higher than the traditional examination. An examination that is sat at a distance need some form of quality assurance to prevent or detect cheating and collusion between candidates. Multiple choice question (MCQ) examinations are of particular interest in assessment. Hence this article focuses on overview of various software’s like LERTAP, The Harpp-Hogan index, Scrutiny!, Integrity and SCheck that can tackle the problem of collusion in online MCQ examination.